The relationship between depression and overactive bladder/urinary incontinence symptoms in the clinical OAB population - Lai, H. Henry; Shen, Baixin; Rawal, Amar; Vetter, Joel (BMC urology, 2016)
Background To investigate the relationship between depression and overactive bladder (OAB)/urinary incontinence symptoms among the clinical OAB population. Methods Patients who were diagnosed with overactive bladder (OAB) and age-matched control subjects without OAB were enrolled. Depression symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS-D). OAB/incontinence symptoms were assessed using the validated questionnaires: ICIQ-UI, ICIQ-OAB, UDI-6, IIQ-7, and OAB-q. Results 27.5 % of OAB patients in our study had depression (HADS ≥8), and 12 % of OAB patients had moderate to severe depression (HADS-D ≥11). OAB patients reported significantly higher HADS-D depression scores compared to age-matched controls (5.3 ± 3.9 versus 2.8 ± 3.9, p = 0.004). OAB patients with depression reported more severe incontinence symptoms (ICIQ-UI), greater bother and more impact on quality of life (UDI-6, IIQ-7) compared to OAB patients without depression ( p = 0.001, 0.01, <0.001, respectively). However there were no differences in ICIQ-OAB and OAB-q. Among OAB patients, there were positive correlations between the severity of depression symptoms and OAB/incontinence symptoms ( p -values <0.001 to 0.035). Conclusions 27.5 % of OAB patients have depression. OAB patients with depression reported more severe urinary incontinence symptoms, greater bother and more impact on quality of life compared to those without depression. Future studies are needed to further examine the mechanistic links between depression and OAB/urinary incontinence.